Financiamento à inovação no Brasil: análise das trilhas de financiamento adotadas por startups de startups de software - Mateus Carneiro dos Santos e Silva (2022)
This master thesis aims to investigate and discuss the access to resources for innovation available in Brazil, especially in the context of startups. The main objective of this work is to identify the main types of funding for innovation that exists in Brazil and that are more adherent to innovative technology companies (software startups) in each of their respective stages of development. As a starting point, a literature review was conducted, which reinforced the importance of funding in the context of technological entrepreneurship, pointed out the difficulties companies have in reaching these resources that are so important, and gave indications of some characteristics valued by funding sources when granting resources. In this context, we began the investigation of the entrepreneurial (and financing) trajectories of 12 software Startups operating in Brazil and abroad. Structured interviews were carried out with the founders of the startups, with the objective of understanding the following elements: i) which sources of funding were accessed at each stage of the company's development; ii) how much funding was raised from each of these sources; iii) which characteristics, in the entrepreneurs' perspective, were the most important for the respective startups to be successful in their fundraising. Based on the collected results and by applying the roadmapping methodology, the information was organized, allowing the construction of several analyses that supported the conclusions of this research. The analysis allowed to identify, in the investigated context, and through the perspectives of the entrepreneurs, the preferred characteristics of each financing source. Furthermore, the present research evidenced the importance that third party funding has in the trajectory of the startups, as well as highlighted some characteristics that, apparently, can be determinant for the success of a software startup in its fundraising process. Based on the results of this work, and on its contributions, it is hoped that future entrepreneurs in their own fundraising process may be more successful in their initiatives.